FACINE re-configuring the Filipino in film in the west, its challenges and possibilities - Tumbocon, Maurio Feria Jr (Plaridel, 2017)
Access online through this link: https://www.plarideljournal.org/article/facine-re-configuring-the-filipino-in-film-in-the-west-its-challenges-and-possibilities